Transformasi dan Kajian Etnopedagogi Naskah Wawacan Sulanjana - Dingding Haerudin; Dedi Koswara (Jurnal Lektur Keagamaan, 2017)
This paper examines the results of the transformation of the Ancient Sundanese script entitled "Wawacan Sulanjana" transliterated in the first stage into the form of prose stories, poetry, and dialogue as a teaching material at school. A recent study shows that the ethnopedagogic values contained in the Ancient Sundanese script of Wawacan Sulanjana, among them imply ten points in which humans as creatures created by the Almighty: 1) must believe in the existence of fate and obedience to all his commandments, 2) to love his or her fellow human beings and not to deceive the weak creatures, 3) to preserve the environment and to cultivate them in order to benefit and to survive as well as the plants; 4) to distinguish between the right and the mistaken; 5) must maintain the mandate entrusted to him or her, 6) must defend the weak and combat injustice, 7) must respect the prevailing cultural customs in a community environment, 8) have the knowledge and skills to navigate life, 9) must prioritize the common interests and not selfish, 10) must be honest and firm and not breaking the promise. This research uses descriptive method, where data transformation result is studied on its elements. For prose and dialogue, we pay attention to the theme, the message, the plot/plot, the background, and the qualities of the character. As for poetry we pay attention to taste, tone, theme, and its mandate. From this study also we obtain twelve titles of prose narrative, twelve titles of dialogue, and twelve kinds of poems. Keywords: codex, transformation, ethno-pedagogy, Sundanese Tulisan ini mengkaji hasil transformasi (alih wahana) naskah Sunda Kuno yang berjudul “Wawacan Sulanjana” hasil transliterasi pada tahap pertama ke dalam bentuk cerita prosa, puisi, dan dialog sebagai bahan pengajaran di sekolah. Sebuah penelitian yang baru-baru ini kami lakukan menunjukkan bahwa nilai-nilai etnopedagogik yang terkandung dalam naskah Sunda Kuno Wawacan Sulanjana, di antaranya mengisyaratkan sepuluh poin di mana manusia sebagai mahluk yang diciptakan Yang Maha Kuasa: 1) harus meyakini akan adanya takdir dan dan taat kepada segala perintahNya,2) harus mengasihi sesama mahluk dan jangan memperdaya mahluk yang lemah, 3) harus memelihara lingkungan sekitar dan mengolahnya agar dapat mengambil manfaat serta mampu bertahan hidup serperti terhadap tanaman, 4) harus membedakan antara yang hak dan yang bathil,5) harus menjaga amanat yang dipercayakan kepada dirinya, 6) harus membela yang lemah dan memerangi ketidakadilan, 7) harus menghormati adat budaya yang berlaku di suatu lingkungan masyarakat, 8) memilki ilmu pengetahuan dan keterampilan untuk mengarungi kehidupan, 9) harus mengutamakan kepentingan bersama jangan mementingkan diri pribadi, 10) harus jujur dan teguh serta tidak melanggar janji. Penelitian ini menggunakan metode deskriptif, di mana data hasil transformasi dikaji unsur-unsurnya. Untuk karangan prosa dan dialog, kami memperhatikan tema, amanat, plot/alur, latar, dan watak atau karakter tokoh. Sementara untuk puisi kami memperhatikan rasa, nada, tema, dan amanat. Dari hasil penelitian ini juga diperoleh dua belas judul karangan prosa narasi, dua belas judul karangan jenis dialog, dan dua belas karangan jenis sajak. Kata kunci: naskah kuno, transformasi, etno-pedagogi, Sunda